Onchocerciasis (River Blindness) 2: control and elimination - Hopkins, MBE, Adrian (Henry Stewart Talks, 2020)
Onchocerciasis control and the elimination of transmission, A programmatic approach, Where are we, where do we want to be, and how do we get there, Understanding the Criteria for elimination, National ownership, Elimination mapping, Coordination with other NTD programmes, Development of Human Resources and Infrastructure development, Alternative strategies, Advocacy and Funding